The impact of environmental regulations on forest product trade in China. (24th July 2019) - Zhang, Yijing; Luo, Wen; Duan, Xinyun; Gao, Lan
Abstract: Forest product trade plays an important role in the development of the Chinese forest industry. The trading value of forest product has shown a yearly growth rate of 12% during the last five recent years. Stringent environmental regulations in China have a profound impact on raw material supplies and industrial production in the forest sector; however, their impact on the forest product trade is still unclear. This study applies fixed and random effects models as well as a seemingly unrelated regression model to investigate the impact of environmental regulations on the trade of forest product from 2002 to 2015. The results indicate that the stringent environmental regulations promoted the import but restricted the export of forest product in general. Specifically, the stringent environmental regulations stimulated the import but had an ambiguous impact on the export of the paper product. The stringent environmental regulations had also stimulated the import of wood product but inhibited the export. In contrast, wooden furniture had been affected minimally; only export got slightly negatively affected by environmental regulations. Recommendations for resource managers: Trade‐offs between economic growth and environmental regulations are needed to smoothly promote the forest product trade in China. Paper and wooden furniture product sectors are less likely to be affected by stringent environmental regulations, because high value‐added products could compensate for environmental costs. The wood product sector is more likely to be negatively affected by stringent environmental regulations because environmental costs could severely impact the competitiveness of low value‐added products.